2016
DOI: 10.1002/14651858.cd012163.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Six-month therapy for abdominal tuberculosis

Abstract: BackgroundTuberculosis (TB) of the gastrointestinal tract and any other organ within the abdominal cavity is abdominal TB, and most guidelines recommend the same six-month regimen used for pulmonary TB for people with this diagnosis. However, some physicians are concerned whether a six-month treatment regimen is long enough to prevent relapse of the disease, particularly in people with gastrointestinal TB, which may sometimes cause antituberculous drugs to be poorly absorbed. On the other hand, longer regimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 15 publications
2
46
0
8
Order By: Relevance
“…Apart from including only adults, two of the three studies included only those with intestinal involvement, which may not be applicable to children where the majority has involvement of multiple abdominal sites. Moreover, the authors of the review have conceded that the quality of evidence regarding the relapse estimate is very low, which is a big concern . Hence, till some robust pediatric data are available, we plan to continue treatment for 9–12 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from including only adults, two of the three studies included only those with intestinal involvement, which may not be applicable to children where the majority has involvement of multiple abdominal sites. Moreover, the authors of the review have conceded that the quality of evidence regarding the relapse estimate is very low, which is a big concern . Hence, till some robust pediatric data are available, we plan to continue treatment for 9–12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Even though a review of three randomised controlled trials comprising 328 adult participants found a 6-month regimen to be efficacious, we believe it cannot be extrapolated to children. 26 Apart from including only adults, two of the three studies included only those with intestinal involvement, which may not be applicable to children where the majority has involvement of multiple abdominal sites. Moreover, the authors of the review have conceded that the quality of evidence regarding the relapse estimate is very low, which is a big concern.…”
Section: Discussionmentioning
confidence: 99%
“…Cochrane researchers examined the available evidence up to the September 2, 2016 and concluded that 6-month regimens are probably as good as 9-month regimens in terms of numbers of people cured but more studies are needed for making confident conclusions. 8 Drug toxicity is a point of concern which requires a close follow up. In this study, eight patients (10.5%) developed hepatotoxicity due to ATT, seven out of whom tolerated either sequential reinitiation of ATT or modified ATT.…”
Section: The Diagnostic Conundrum Of Crohn's Disease and Intestinal Tbmentioning
confidence: 99%
“…Zusammenfassend empfehlen die Autoren/innen eine 6-monatige Therapie wie bei einer pulmonalen Tuberkulose. Die ersten beiden Monate sollte eine vierfache Kombination, bestehend aus Isoniazid, Rifampicin, Pyrazinamid und Ethambutol, gegeben werden, gefolgt von viermonatiger Behandlung mit Isoniazid und Rifampicin [48]. Eine Gefahr stellen die weltweit ansteigenden Zahlen von resistenten Mykobakterien dar [1].…”
Section: Therapieunclassified